Herbal-based Traditional Medicinal Knowledge of Local Inhabitants in Rudraprayag District of Uttarakhand, India - Chandra, Kailash; Nautiyal, Bhagwati Prasad; Nautiyal, Mohan Chandra (Ethnobotany Research and Applications, 2013)
Traditional medicinal knowledge has gained much attention recently due to rejuvenation of faith in traditional system of medicines. The Indian Himalaya is a source of plant based indigenous medicinal knowledge based on local plant diversity. Surveys were conducted in Rudraprayag district of Uttarakhand, India to collect indigenous information on primary health care. 29 formulations using 159 plant species were recorded treating 119 ailments in 13 broad therapeutic classes. Results have been compared with traditional knowledge from other parts of India.